Treino parental e sua influência sobre os marcos do desenvolvimento em crianças no transtorno do espectro do autismo atendidas em caps infantil - Moura, Conceição de Maria Aguiar Barros (Universidade do Vale do Rio dos Sinos, 2025)
This PhD thesis of the Postgraduate Program in Collective Health at UNISINOS aimed to analyze the effectiveness of parental training interventions of basic skills in the developmental milestones of autistic children treated at a children's CAPS. The aim was to verify whether the training carried out with the participants was effective and to analyze the developmental milestones of autistic children aged two to six, using the Operationalized Portage Inventory (IPO), before and after the interventions conducted by the parents. Article 1 presented the methodological aspects of a non-randomized clinical trial on the implementation and adaptation of an intervention protocol mediated by parents of autistic children treated at the CAPSij in a city of Maranhão. Regarding the results, it is noteworthy that the reference protocol is an appropriate instrument to guide health professionals in advising parents of autistic children, as it covers the basic skills to be taught, presented in a simple and illustrative manner and, more importantly, because it indicates the development of the target skills in children with ASD. Article 2 analyzed the effectiveness of parental basic skills training interventions on the developmental milestones of children with autism spectrum disorder (ASD) treated at a children's CAPS. Two groups were investigated (an intervention group (Group A) and a control group (Group B)), balanced in terms of the child's developmental age, race/color, family income, and the primary caregiver's level of education. The study demonstrated that children in group B presented significant differences in the comparison of scores before the beginning of the study and after the follow-up period only for the language domain (T0 = 1.32 vs. T1 = 1.53; p = 0.036). On the other hand, in group A, all development domains showed significant improvements after follow-up. In summary, the results of this thesis corroborate the effectiveness of parental training in improving the developmental milestones of children with ASD who received educational interventions over six months, demonstrating that this type of intervention can be replicated both within the SUS (Brazilian Unified Health System) and in private services that take care of autistic children. Children in the intervention group experienced significant improvements in socialization, language, cognition, self-care, and motor skills, demonstrating that parent-mediated interventions, even in public settings (SUS), are effective and can contribute to improving the lives of autistic children and their families.
Keywords: Transtorno do Espectro do Autismo; Desenvolvimento infantil; Educação em saúde; Terapia comportamental; Serviços de saúde mental; Sistema Único de Saúde; Autism Spectrum Disorder; Child development; Health education; Behavioral therapy; Mental health services; Unified Health System; ACCNPQ::Ciências da Saúde::Saúde Coletiva